Polyvinyl alcohol films incorporating cellulose nanocrystals, chitosan, and mesoporous silica nanoparticles for enhanced stability and controlled release of beet extracts - Solmaz Pourbarghi Soufiani; Shima Yousefi; Masoud Honarvar; Weria Weisany; Gholamhassan Asadi (Carbohydrate Polymer Technologies and Applications)
Despite advancements in polymer-based sustainable materials, developing food packaging that balances mechanical strength, flexibility, antioxidant activity, solubility, and antibacterial efficacy remains challenging. This study examines the effects of chitosan (CH), mesoporous silica nanoparticles (MSNPs), cellulose nanocrystals (CNC), and beet extract (BE) on biodegradable films. LC-MS analysis identified Pirola beet extract as the richest source of antioxidants, particularly 7-hydroxymatairesinol (20.56 %) and apigenin derivatives (15.07 %). Films containing 2 % CH, 2 % MSNPs, 1 % CNC, and 15 % BE exhibited the highest antioxidant activity (52.97 µmol) and improved solubility (4.20 g m⁻²). Water vapor permeability remained stable (1.07–1.14 g mm m⁻² day kPa), while tensile strength peaked at 36.20 MPa in films with 2 % CH, 0 % MSNPs, and 0.5 % CNC. Elastic modulus reached 1.33 MPa, and elongation improved with CNC, achieving 55.96 % in films with 1 % CNC and 10 % BE. The strongest antibacterial efficacy was observed in films with 2 % CH, 2 % MSNPs, 1 % CNC, and 15 % BE, significantly inhibiting Staphylococcus aureus and Listeria monocytogenes. These findings highlight the potential of these films to enhance food preservation, extend shelf life, and reduce environmental impact, underscoring the need to optimize component concentrations for multifunctional, sustainable packaging solutions.